A Three-dimensional Model Establishment of Multiple Connecting Leaders Initiated from Tall Structures - Yu Junhao; Tan Yongbo; Zheng Tianxue; Wang Yiru; Shi Zheng (应用气象学报)
A new model for simulating multiple upward leaders initiated from tall structures in cloud-to-ground (CG) lightning flash is established, in which the initiation and development module of are implanted in the existing 3D stochastic parameterization of leader attachment process, using electric field parallel computing technology to improve the simulation efficiency. The new model is applied to simulate real CG lightning and is compared with observation results of statistical data and leader morphological characteristics. Several model output parameters include the length of upward unconnected leaders (UULs), the inception height of UULs, horizontal distance between the strike point and the UUL's inception point, 3D distance between the nearest tip of the downward leader branches and the UUL's inception point when the UUL is initiated. Values range from 12 m to 709 m, 360 m to 600 m, 255 m to 1026 m, 326 m to 589 m, which are in high agreement with the observation. The new model can represent characteristics that UUL starts earlier than upward connected leaders (UCL) and channels of UUL are straight in a real CG lightning case F1215. It can also simulate 4 typical connecting behaviors which are observed in natural CG lightning flash, including the tip of downward leader (DL) to the tip of upward connecting leader (UCL) and the DL's tip to the lateral surface of UCL in cases where one or more upward leaders starts. The comparison with the observation proves that the simulation is reasonable to some extent and provides a basic model. By analyzing the simulated CG lightning data and morphological characteristics, it shows that the highest tower can protect a certain area of buildings nearby and attract more distant downward leader branches. The inception of multiple upward leaders and the strike point of last jump are influenced by the distribution, height of high structures and the initial position of the DL, which are of great significance to the lightning protection.